Development of a user friendly mechanical seal trap for sanitary latrines / Syed Azizul Haq, PEng - Syed, Azizul Haq, PEng (2012)
The new mechanical seal trap is devised by attaching a flap hinged at the top of the outlet of the trap. The outlet shall remain almost vertical. The vertically suspended flap will keep the outlet end always closed and thus prevent ingress of foul gases in the latrine. Flowing excreta waste will push the flap to pass through and the flap will automatically get back to its original position afterwards. Three types of such trap have been developed for fitting with vertical, horizontal and 450 draining outlets. To fit with vertical draining outlet, the mechanical seal trap is developed by fixing the hinged flap at the outlet of a 450 elbow. For fitting with horizontal drainage outlet the trap has been developed by fixing the hinged flap at the outlet end of a short piece of pipe having an inlet bell only and for fitting with 450 draining outlet the trap is made having the outlet at an angle of 450 . This idea of mechanical seal trap instead of water seal trap will help achieve the desired sanitation, particularly in pour flush latrine. These types of mechanical trap can also be used in mobile toilets, bus toilets etc. where flushing is limited.